Breast cancer in BRCA mutation carriers: breast-conserving therapy or bilateral mastectomy?. (November 2013) - Murphy, James O; Sacchini, Virgilio S
SUMMARY BRCA mutation carriers who are diagnosed with breast cancer can be overwhelmed with decisions. The choice between breast-conserving therapy, mastectomy or a bilateral mastectomy is often the first to be made by patients. Those who choose breast-conserving therapy are faced with an increased risk of ipsilateral breast tumor recurrence and contralateral breast cancer; however, choosing more extensive surgery increases surgical morbidity without a proven survival advantage. Additional factors that influence surgical decision-making are the use of adjuvant therapy, the role of risk-reducing salpingo-oophorectomy and the biology of the breast cancer. Advances in surgical techniques, breast reconstruction and screening must also be considered when choosing the surgical treatment for breast cancer patients with a BRCA mutation.